2012
DOI: 10.1021/ml200299g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biochemical Evaluation of Thiochromanone Thiosemicarbazone Analogues as Inhibitors of Cathepsin L

Abstract: A series of 36 thiosemicarbazone analogues containing the thiochromanone molecular scaffold functionalized primarily at the C-6 position were prepared by chemical synthesis and evaluated as inhibitors of cathepsins L and B. The most promising inhibitors from this group are selective for cathepsin L and demonstrate IC 50 values in the low nanomolar range. In nearly all cases, the thiochromanone sulfide analogues show superior inhibition of cathepsin L as compared to their corresponding thiochromanone sulfone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…5 Almeida et al noted that thiacycloalkynes (C) are promising new reagents for click chemistry. 6 Furthermore, thiosemicarbazone analogues (D) were found to be potent inhibitors of cathepsin L, 7 whereas in the synthesis of bryostatin, which is used in the treatment of lymphoma, sulfones (E) serve as central glycal intermediates. 8 In addition, 2,6,7-trioxabicyclo-[2.2.2]octane sulfone (F) is a new reagent that enables the rapid assembly of pyranone intermediates.…”
mentioning
confidence: 99%
“…5 Almeida et al noted that thiacycloalkynes (C) are promising new reagents for click chemistry. 6 Furthermore, thiosemicarbazone analogues (D) were found to be potent inhibitors of cathepsin L, 7 whereas in the synthesis of bryostatin, which is used in the treatment of lymphoma, sulfones (E) serve as central glycal intermediates. 8 In addition, 2,6,7-trioxabicyclo-[2.2.2]octane sulfone (F) is a new reagent that enables the rapid assembly of pyranone intermediates.…”
mentioning
confidence: 99%
“…In fact, the thiosemicarbazide itself was inactive against Leishmania parasites. Therefore, despite the available information, it cannot be deduced that acylhydrazone derivatives always act as prodrugs [28,29], since it has been shown that several hydrazones are inhibitors of cysteine proteases [16,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Structures of thiochroman-4-ones ( [1][2][3][4][5] and hydrazone derivatives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some 3-substituted thiochromanones have an antifungal effect on many fungi in vitro such as Trichophyton rubrum, Machaeranthera gypsum, Cryptococcus neoformans, Candida krusei, Epidermophyton floccosum and S. schenekn, and show a similar or higher level of activity when compared with fluconazole [4,5]. In recent years, it has been reported that some thiochromanones have anticancer activities, because they can act as potent inhibitors of cathepsin L which is a unique biomolecular target in anticancer drug development [6,7]. (Z)-3-(chloromethylene)-6-flourothiochroman-4-one (CFO) is one of thiochromanone derivatives that exhibits noticeable antitumor activities due to inducing apoptosis of tumor cells by triggering caspase cascade and increasing expression of death receptor 3 (DR3) [8].…”
Section: Introductionmentioning
confidence: 99%